Rentabilidad en la empresa de transporte Inlogtrans S.A. del cantón Yaguachi en los períodos 2021-2022. - Moran Murillo, Lidiana Doménica (2023)
The present study is based on the analysis of profitability in a cargo transportation company, it is essential due to its importance in strategic decision making and the long-term survival of the company, this analysis is fundamental, some of the topics developed are summarized below. Resource Optimization: Freight transportation is a highly competitive and expensive sector. A profitability analysis allows the company to identify areas where resources, such as the vehicle fleet, routes, personnel and fuel, can be optimized to reduce operating costs. Informed Decision Making: With a profitability analysis, company management can make decisions based on concrete data. This includes decisions related to expansion, acquisition of new assets, investments in technology and pricing strategies. Cost Control: Allows more effective control of operating and variable costs, which may include vehicle maintenance, fuel, insurance, labor costs and other expenses related to fleet operation. Financial Planning: Enables more accurate financial planning by providing estimates of future revenues and costs. This is essential to ensure the financial stability and investment capacity of the company